ANALISIS YURIDIS PUTUSAN HAKIM TERHADAP OKNUM APARAT KEPOLISIAN YANG MELAKUKAN TINDAK PIDANA NARKOTIKA - Regita Triana Aulia; Mukhlis R; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This narcotics problem has reached an alarming level, the distribution of narcotics inIndonesia has a tendency to increase and it is very unfortunate that narcotics users anddealers are currently being carried out by law enforcement officials, one of which is membersof the police. Based on Article 13 of Law Number 2 of 2002 concerning the Police, one of theduties of the police is to enforce the law, especially in eradicating narcotics, but the fact isthat there are still police officers who are involved in this narcotics crime, therefore thepunishment given must be heavier than ordinary people . However, the verdict handed downby the judge even imposed a sentence below the minimum limit. The existence of the judge'sdecision is very influential on justice. The purpose of this study is to find out and analyze thebasic considerations of judges against police officers who commit narcotics crimes andformulate ideally the imposition of criminal sanctions given by judges to police officers whocommit narcotics crimes for the future.The type of research that will be used in this research is normative juridical in nature,the source of the data used is secondary data obtained through library materials consistingof primary, secondary and tertiary legal materials. In collecting data for research usedlibrary research methods. This research also used qualitative data analysis and produceddescriptive data using deductive thinking methods.From the results of the research, First, the basis for the judge's consideration of thepolice officers who commit narcotics crimes is described based on juridical and non-juridicalconsiderations. In this case the judge is also guided by SEMA Number 3 of 2015 concerningEnforcement of the Results of the Plenary Meeting of the Supreme Court Chamber of 2015 asa Guideline for the Implementation of Tasks for the Court to become the basis for the panelof judges in imposing below minimum sentences in decisions related to police officers whocommit narcotic crimes. Second, Ideally, the imposition of criminal sanctions given by judgesto police officers who commit narcotics crimes for the future in Law Number 35 of 2009concerning Narcotics requires rules regarding the weighting of special penalties given to lawenforcement officials who become users or dealers of narcotics with impose criminalsanctions on users and dealers with an additional 1/3 (one third) imprisonment consideringthat these perpetrators are police officers who are supposed to enforce the law.Keywords: Narcotics Crime - Police Officers - Judges Decision